Literature review of comparative school-to-work research: How institutional settings shape individual labour market outcomes - Anna Marczuk (Journal for Labour Market Research, 2024)
Comparative school-to-work research has long emphasised the role of institutions in shaping youth labour market integration. This paper provides an overview of this research stream, consisting of four main sections. The first section introduces a variety of labour market outcomes of young graduates within Europe and identifies country clusters with higher and lower outcomes; this empirical evidence has so far remained limited in the multivariate oriented research stream. The second section links these labour market outcomes to the institutional settings of the education systems prevalent in the country clusters. By considering a wide country sample, it introduces a reliable country classification of transition regimes (along the OLM-ILM continuum), which has so far been partly inconclusive in research. The third section links labour market outcomes in turn to labour market institutions of the country clusters. This section emphasizes why labour market institutions drive only particular individual outcomes. Finally, the fourth section connects the previous three: it describes how certain institutional complementarities affect the youth labour market integration in the identified European country clusters. The review further identifies theoretical inconclusiveness or data-related desiderata, for which recommendations and solutions are proposed. The paper thus aims to assist both familiar and unfamiliar researchers to access the research stream by offering a comprehensive introduction and clear country classifications, linking research streams, and providing solutions to identified issues.
Keywords: 330; Labour market; Comparative research; Complementarities of institutions; Education system; Institutional settings; School-to-work transitions